2017
DOI: 10.1515/bjdm-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

3D printing guide implant placement: A case report

Abstract: SummaryBackground:Cone Beam Computer Tomography (CBCT) is representing a new concept of radiological diagnostics and its application occupies a special place in implantology. Today, preoperative planning, and quantitative and qualitative jaw bone analysis cannot be done without the use of these techniques. The latest in a series of achievements in this field is a method of making a guide for implant using a 3D printing technique. This way pre implantology planning reduces the chance of surgical complications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The introduction of osseointegrated titanium implants back in 1965 resulted in the expansive development of implantology [ 6 ]. Numerous studies have shown that implant therapy is considered a predictable type of dental therapy with a very high average success rate of around 90–95% [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of osseointegrated titanium implants back in 1965 resulted in the expansive development of implantology [ 6 ]. Numerous studies have shown that implant therapy is considered a predictable type of dental therapy with a very high average success rate of around 90–95% [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might create a problem in esthetic and function because of lateral forces transmitted to implant. 1 With the advancement in computer-guided surgical techniques, it has become possible to improve implant positioning, prevent injuries to important anatomical structures such as mandibular nerve, improve functional and aesthetic outcome of the prosthesis, and reduce operative time and post-operative discomfort. 2,3 The conventional method of pre-operative planning includes the radiographic assessment of the available bone by periapical and panoramic radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…This surgical stent has sleeves that correspond to the diameter of drills or implant. 1 The surgical stent is tooth supported, mucosa supported, or bone supported. The tooth-supported stent is more accurate than mucosasupported stent.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical guides created by 3D printing can be used to accurately place dental implants in the jawbone, which can help to reduce the risk of complications and improve the overall success of the surgery. For example, there is a case report by Zoran et al in which a guide was created by 3D printing technique for implant placement [116]. Its results showed that, considering both surgical and prosthetic aspects, the 3D-printed surgical guide could facilitate having an optimal positioning of the implant [116].…”
mentioning
confidence: 99%
“…For example, there is a case report by Zoran et al in which a guide was created by 3D printing technique for implant placement [116]. Its results showed that, considering both surgical and prosthetic aspects, the 3D-printed surgical guide could facilitate having an optimal positioning of the implant [116].…”
mentioning
confidence: 99%